Praxeological Analysis of the Mathematics Textbook on the Topic of Translation - Maifa, Talisadika Serrisanti; Fatimah, Siti; Suryadi, Didi (Proceeding International Conference on Mathematics and Learning Research, 2024)
This study analyzes the sequence of tasks in the Mathematics textbook to identify learning obstacles associated with the concept of translation, with a specific focus on the definition of translation. This analysis employs the theory of praxeology, a key concept in the Anthropological Theory of Didactics (ATD). The findings highlight three potential didactical obstacles and one potential epistemological obstacle within the task sequence. Therefore, these findings should be considered by teachers to anticipate and minimize potential obstacles in teaching the concept of translation.